Refocusing of B-cell responses following a single amino acid substitution in an antigen - Simmons, Cameron (2018)
Intranasal immunization of BALB/c strain mice was carried out using baculovirus-derived human chorionic gonadotrophin (hCG) beta-chain, together with Escherichia coli heat-labile enterotoxin. Gonadotrophin-reactive immunoglobulin A (IgA) was induced in a remote mucosal site, the lung, in addition to a systemic IgG response. The extensive sequence homology with luteinizing hormone (LH) results in the production of LH cross-reactive antibodies when holo-hCG is used as an immunogen. In contrast to wild-type hCGbeta, a mutated hCGbeta-chain containing an arginine to glutamic acid substitution at position 68 did not induce the production of antibodies which cross-react with LH. Furthermore, the epitopes utilized in the B-cell response to the mutated hCGbeta shifted away from the immunodominant region of the parent wild-type molecule towards epitopes within the normally weakly immunogenic C terminus. This shift in epitope usage was also seen following intramuscular immunization of rabbits. Thus, a single amino acid change, which does not disrupt the overall structure of the molecule, refocuses the immune response away from a disadvantageous cross-reactive epitope region and towards a normally weakly immunogenic but antigen-unique area. Similar mutational strategies for epitope-refocusing may be applicable to other vaccine candidate molecules.